Advanced multiple sclerosis and the psychosocial impact on families. - Bowen C; MacLehose A; Beaumont JG (Psychology & Health, 2011)
This study explores family relationships and support needs when adapting to a relative's advanced-multiple sclerosis (MS) around transition into care. A multi-site qualitative study of relatives of people with advanced-MS was conducted. A purposive sample of 25 relatives was selected and interviewed either in the care home or participants' homes. Interviews were recorded, transcribed and analysed using grounded theory methodology and Atlas.ti 5.2 software. Data quality enhancement involved: a self-report questionnaire; triangulation and member-checking. Themes derived from the data were: information, communication and understanding; family relationships, roles and responsibilities; emotions, coping and support; life outlook and reflection. Provision of information and support for families around the transition into care appears to be inconsistent despite there being a need for family members to ask questions and discuss the impact of the condition. Relatives reported that as a family and as individuals they faced significant challenges and were in great need of support at times, but reflected that they would have found it very difficult to accept. Relatives were also often unsure what type of support would have helped. For care providers, there needs to be a shift from the traditional health care professional 'patient-centred' mindset towards more proactive family-centred approaches and steps to encourage this are articulated.